1998
DOI: 10.1111/j.1574-695x.1998.tb01136.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimycobacterial activity of chemically defined natural substances from the Caribbean flora in Guadeloupe

Abstract: Eight chemically defined, naturally occurring compounds were extracted from the tropical flora of the Caribbean island of Guadeloupe: pilocarpine, an alkaloid from Pilocarpus racemosus ; heraclenol and isomeranzin, coumarins from Triphasia trifolia; lochnerin, an indole alkaloid from Rauwolfia biauriculata; ibogaine and voacangine, indole alkaloids from Tabernaemontana citrifolia ; texalin, an oxazole from Amyris elemifera; and canellal, a sesquiterpene dialdehyde from Canella winterana. An essential oil fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 14 publications
3
37
0
2
Order By: Relevance
“…It has been used in treatment of muscular and nervous asthma, respiratory depression and type III poliovirus (HPV-3). Consistently, another two indole alkaloids, ibogaine and voacangine, isolated from another member of Tabernaemontana genus (T. citrifolia) have been reported for their antimycobacterial activity against Mycobacterium tuberculosis H37Rv (MIC 50 g/mL) (Rastogi et al, 1998). In addition, the aqueous extract of the roots of Tabernaemontana elegans was also found to be active against Mycobacterium smegmatis ATCC 14468 at MIC 1 mg/mL, and the presence of alkaloids was detected by a preliminary phytochemical study (Pallant and Steenkamp, 2008).…”
Section: Preliminary Phytochemical Investigationmentioning
confidence: 65%
“…It has been used in treatment of muscular and nervous asthma, respiratory depression and type III poliovirus (HPV-3). Consistently, another two indole alkaloids, ibogaine and voacangine, isolated from another member of Tabernaemontana genus (T. citrifolia) have been reported for their antimycobacterial activity against Mycobacterium tuberculosis H37Rv (MIC 50 g/mL) (Rastogi et al, 1998). In addition, the aqueous extract of the roots of Tabernaemontana elegans was also found to be active against Mycobacterium smegmatis ATCC 14468 at MIC 1 mg/mL, and the presence of alkaloids was detected by a preliminary phytochemical study (Pallant and Steenkamp, 2008).…”
Section: Preliminary Phytochemical Investigationmentioning
confidence: 65%
“…Isolated alkaloids from various Tabernaemontana species: conoduramine, conodurine, and voacamine, possess strong antibacterial activity against Grampositive bacteria (Van Beek et al, 1984;1985). The alkaloids ibogamine and voacangine have proven antimycobacterial activity (Rastogi et al, 1998). None of these compounds, however, have been previously identified in T. elegans, suggesting that the pharmacophore responsible for the antibacterial activity may be common to a number of alkaloids in this genus.…”
Section: Resultsmentioning
confidence: 99%
“…Voacangine has been reported to have cardiovascular toning, central nervous system depressant, anti-convulsive, anti-pyretic, analgesic, local anesthetic, acetyl cholinesterase inhibitory [82], anti-angiogenic [83] and anti-mycobacterial [84] activities. Studies have shown that echitamine has diuretic, hypotensive [85], central nervous system depressant and antiepileptic [86] properties.…”
Section: Discussionmentioning
confidence: 99%